A Few Methods for Estimating Life Expectancy: Methods for Estimating Life Expectancy - Phukon, M.; Ahamed, M. I. (Journal of Scientific Research, 2019)
In this paper, firstly, an extensive empirical investigation is done by fitting linear regressions exhaustively to observe the pattern and nature of linear relationships of life expectancies of each age-group with that of all other age-groups in fifty-four Sample Registration System (SRS) life tables of Assam state of India. Secondly, two second degree polynomial regression models have been proposed for estimating life expectancies at birth (e0). Both the models have been empirically illustrated in fifty-four SRS life tables of India and fifty-four SRS life tables of each of 16 major Indian states. The estimated values of e0 are examined in relation to estimated values of the same by some other methods and e0 values available in SRS tables of the years 2001-05 and 2011-15. Moreover, e0 values for all districts of Assam are estimated by using one of the proposed polynomial regressions together with some indirect techniques of estimation.